The Implementation of the Storyline Approach in EFL Writing Instruction: A Case Study of Teacher Practices and Student Responses at SMP Negeri 2 Gorontalo, Indonesia - Tresmina Paputungan; Kartin Lihawa; Novriyanto Napu (International Journal of Education, Culture, and Society, 2026)
This study investigates the implementation of the Storyline Approach in English as a Foreign Language (EFL) writing instruction, with a focus on teacher practices and student responses at SMP Negeri 2 Gorontalo. It aims to explore how the Storyline Approach is operationalized in classroom instruction and to examine its impact on students’ writing development and perceptions. Employing a qualitative case study design, data were collected through classroom observations, semi-structured interviews with the English teacher, and document analysis of lesson plans, complemented by analysis of students’ writing scores from pre-tests and post-tests. The findings reveal that the teacher implemented the Storyline Approach systematically through clearly defined stages, including context creation, character and setting development, plot construction, language focus, and reflection, thereby creating a meaningful and contextualized learning environment that actively engaged students in the writing process. Quantitative evidence from students’ writing scores indicates consistent improvement across multiple themes, particularly in grammar, text organization, content development, and coherence. In addition, students demonstrated positive responses toward storyline-based instruction, reflected in increased motivation, participation, and confidence in writing. The study concludes that the Storyline Approach constitutes an effective and sustainable instructional strategy for enhancing EFL writing skills at the junior secondary school level and contributes to the growing body of research on contextual and student-centered approaches in EFL writing instruction in Indonesian educational settings.